Colitis nucleomigrans: The third type of microscopic colitis (part 2). An ultrastructural study. Issue 10 (6th August 2020) - Tachibana, Mitsuhiro; Tsutsumi, Yutaka
Abstract : In the preceding article (part 1), we proposed the third type of microscopic colitis: colitis nucleomigrans (CN). Microscopically, the nuclei of surface‐lining columnar cells were migrated in chain to the middle part of the cells, and apoptotic nuclear debris was scattered in the cytoplasm beneath the nuclei. For ultrastructural analysis, buffered formalin‐fixed biopsy tissue of CN ( n  = 2) was dug out of paraffin blocks. After deparaffinization, tissue blocks were prepared with conventional sequences. Ultrathin sections were stained with uranyl acetate and lead citrate. Fine morphological preservation was satisfactory even after paraffin embedding. Apoptotic nuclear debris was localized within the cytoplasm beneath the migrated nuclei of the surface‐lining columnar cells. Abnormality of cytoskeletal filaments (actin, cytokeratin and tubulin) was scarcely recognized in the epithelial cytoplasm. Macrophages located in the uppermost part of the lamina propria phagocytized electron‐dense globular materials. Intraepithelial lymphocytes with scattered dense bodies were observed among the columnar cells. We suppose that altered apoptotic processes in the colorectal surface‐lining epithelial cells may be involved in the pathogenesis of CN. Mechanisms of nuclear migration to the unusual position or impairment of nuclear anchoring to the basal situation in the surface‐lining epithelial cells remain unsettled, because cytoskeletal components showed little ultrastructural abnormality.